U.S. Department of Veterans Affairs Veterans Justice Outreach Program: Connecting Justice-Involved Veterans With Mental Health and Substance Use Disorder Treatment. (March 2016) - Finlay, Andrea K.; Smelson, David; Sawh, Leon; McGuire, Jim; Rosenthal, Joel; Blue-Howells, Jessica; Timko, Christine; Binswanger, Ingrid; Frayne, Susan M.; Blodgett, Janet C.; Bowe, Tom; Clark, Sean C.; et al.
The Veterans Justice Outreach (VJO) program of the U.S. Veterans Health Administration has a primary mission of linking military veterans in jails, courts, or in contact with law enforcement to mental health and substance use disorder treatment. National data of veterans with VJO contact were used to describe demographic characteristics, and mental health and substance use disorder diagnoses and treatment use and test correlates of treatment entry and engagement using multi-level logistic regression models. Of the 37, 542 VJO veterans, treatment entry was associated with being homeless and having a mental health disorder or both a mental health and a substance use disorder versus a substance use disorder only. Being American Indian/Alaskan Native was associated with lower odds of treatment entry. Engagement was associated with female gender, older age, Asian race, urban residence, and homeless status. Increased utilization of substance use disorder treatment, especially pharmacotherapy, is an important quality improvement target.